2022
DOI: 10.34172/jhp.2022.45
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ulcer effects of cumin (Cuminum cyminum L.), thyme (Thymus vulgaris L.), and caraway (Carum carvi L.) essential oils on peptic ulcer and ulcerative colitis models in rats

Abstract: Introduction: Essential oils are considered a potential alternative to synthetic drugs in the management of diseases such as peptic ulcer (PU) and ulcerative colitis (UC). This study is concerned with comparing the therapeutic effects of Cuminum cyminum L, Carum carvi L, and Thymus vulgaris L. essential oils on PU and UC models induced by ethanol. Methods: Rats were divided into 10 groups; control groups were treated with saline and experimental groups with 500 mg/kg body weight of C. cyminum, C. carvi, or T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…To profile T . vulgaris essential components, gas chromatography-mass spectrometry (GC/MS) analysis was carried out according to the methods described earlier [ 32 ]. Gas chromatography analysis was performed on Agilent GC/MS (model GC6890/ MS5973 / USA) with DB-5MS UI capillary column (60m × 0.25mm OD × 0.25μm film thickness).…”
Section: Methodsmentioning
confidence: 99%
“…To profile T . vulgaris essential components, gas chromatography-mass spectrometry (GC/MS) analysis was carried out according to the methods described earlier [ 32 ]. Gas chromatography analysis was performed on Agilent GC/MS (model GC6890/ MS5973 / USA) with DB-5MS UI capillary column (60m × 0.25mm OD × 0.25μm film thickness).…”
Section: Methodsmentioning
confidence: 99%
“…Lactating mothers use caraway to enhance the flow of breast milk [10]. The EO and caraway extracts are proven to have antidiabetic, antioxidant, hepatoprotective, antiulcerogenic, antimicrobial, insecticidal, diuretic, analgesic, renoprotective, molluscicidal, anti-cholinesterase, and immunomodulatory activities [27,28].…”
Section: Carawaymentioning
confidence: 99%
“…Accordingly, studies have shown that ingestion of CCS extracts caused a significant reduction of lipid peroxidation (lower MDA levels) in animal models had chemical-mediated oxidative stress. [52][53][54] A healing tissue in repaired wounds produces increased collagen protein, as one of the essentials required for tissue regeneration and for the final two stages of wound repair. 4-Hydroxyproline (HXP) is the main amino acid of collagen that comprises nearly 13.5% of its amino acid content which allows collagen twisting helix to maintain its integrity and structural stability.…”
Section: Ccs Effects On Hydroxyprolyinementioning
confidence: 99%
“…While rats receiving intrasite gel or methanolic extracts of CCS had significantly reduced values of MDA, denoting antioxidant potentials of these agents against oxidative damages that would otherwise delay the wound healing process. Accordingly, studies have shown that ingestion of CCS extracts caused a significant reduction of lipid peroxidation (lower MDA levels) in animal models had chemical‐mediated oxidative stress 52–54 …”
mentioning
confidence: 99%
See 1 more Smart Citation